2015
DOI: 10.1111/1748-8583.12072
|View full text |Cite
|
Sign up to set email alerts
|

How reward satisfaction affects employees’ turnover intentions and performance: an individual differences approach

Abstract: We challenge the assumption that satisfaction with rewards has the same effect on the behaviour and attitudes of every employee, and hypothesise that there are individual differences in the effects of (satisfaction with) financial, material and psychological rewards on turnover intentions and task performance. Survey data from 179 employees are combined with supervisor‐rated task performance data and analysed with cluster‐wise regression analysis. As for task performance, no employee types or individual differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 28 publications
6
64
1
7
Order By: Relevance
“…However, since Cerasoli et al (2014) demonstrate that motivation triggered by financial and non-financial rewards differently impacts the quality and quantity of performance, it is further expected that there is also a unique effect tied to rewards from different reward categories. The latter expectation is further supported by findings from de Gieter and Hofmans (2015), who show that there are differences in the effects of financial, material and psychological rewards. As outlined in the previous section neural findings support the assumption that different rewards have both, overlapping and specific effects.…”
Section: Aim and Hypotheses Of This Studymentioning
confidence: 56%
See 1 more Smart Citation
“…However, since Cerasoli et al (2014) demonstrate that motivation triggered by financial and non-financial rewards differently impacts the quality and quantity of performance, it is further expected that there is also a unique effect tied to rewards from different reward categories. The latter expectation is further supported by findings from de Gieter and Hofmans (2015), who show that there are differences in the effects of financial, material and psychological rewards. As outlined in the previous section neural findings support the assumption that different rewards have both, overlapping and specific effects.…”
Section: Aim and Hypotheses Of This Studymentioning
confidence: 56%
“…Thus, regarding the current study it is important to note that there are different reward categories and that there is empirical evidence that when organizations offer financial rewards, their employees' performance is likely to improve. However, there seems to be a shortcoming of research regarding non-financial rewards, even though organizations continue to implement these (de Gieter and Hofmans 2015).…”
Section: Rewards As External Factorsmentioning
confidence: 99%
“…The current research is also limited because only commitment is included as the ultimate outcome variable. Receiving performance‐contingent rewards could result in multiple positive outcomes that are relevant to the employee and the firm, such as employees' work performance, satisfaction, and citizenship behavior (e.g., De Gieter & Hofmans, ; Nyberg, Pieper, & Trevor, ). Travel is also known to help rejuvenate and improve individuals' perceived life quality and well‐being (e.g., Uysal, Sirgy, Woo, & Kim, ).…”
Section: Limations and Future Researchmentioning
confidence: 99%
“…While if the reward is not satisfied, employee turnout to change behavior and lead to leave the organization. According to De Gieter & Hofmans [4], found that in past year, many organization having problem of difficulties on attracting and retaining the employee due to the reward that offer from organization in which focus on monetary reward only. When the employees contribute into the organization, they expect that to receive more than monetary reward like appreciation from manager, compliment, flexible working hour and others related.…”
Section: Reward Systemmentioning
confidence: 99%
“…Lastly, the factor that effect turnover intention at this manufacturing company is rewards system. This factor demonstrated that the employees will motivated and encourage to the positive behavior and attitude such as increase the performance if the organization provides sufficient reward to them [4]. [5], turnover is defined as "conscious and deliberate willingness to leave the organization".…”
Section: Introductionmentioning
confidence: 99%